Characterisation of COVID-19 deaths by vaccination types and status in Malaysia between February and September 2021 - Abdul Taib, Nur Asheila; Raja, Dhesi Baha; Kuo, Alvin Jing Teo; Kamarulzaman, Adeeba; William, Timothy; HS, Arvinder-Singh; Mokhtar, Siti Aisah; Choo, Yee Ting; Wei, Aun Yap; Chan, Michelle Yoon Kim; Edwin Amir, Lidwina (Elsevier, 2022)
We report COVID-19 deaths by vaccine types (inactivated whole-virion SARS-CoV-2 [hereinafter inactivated vaccine], BNT162b2, and ChAdOx1 vaccines), and vaccination status in Malaysia and further stratified the analysis by the presence of comorbidities. We used line list data on COVID-19 deaths until 14 September 2021, made available publicly by the Ministry of Health Malaysia.1 We limited the analysis from 24 February 2021 onwards, after COVID-19 vaccines were introduced. For all vaccine types, we defined individuals to be fully vaccinated 14 days after the final dose. We considered individuals who received only the first dose or died within 14 days after the final dose as partially vaccinated. We calculated the age-standardised mortality rate per 100,000 population (ASMR) by the direct method of standardisation using the Malaysian population2 and the World Health Organization (WHO) standard population as reference and their corresponding 95% confidence interval.